2004
DOI: 10.1074/jbc.m400320200
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Repression of Interleukin-12 p40 Transcription by Erythroid Kruppel-like Factor in Macrophages

Abstract: Transcription of interleukin (IL)-12 p40 in myeloid cells is attributed to the recruitment of multiple activated transcription factors such as nuclear factor B (NFB), CCAAT enhancer-binding protein ␤, ets-2, PU.1, and so forth. We now provide the first description of the human erythroid Kruppel-like factor (EKLF) in human primary macrophages and identify the role of EKLF in IL-12 p40 expression. EKLF-specific binding to the CACCC element (؊224 to ؊220) on the human IL-12 p40 promoter was observed in resting hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 55 publications
0
35
0
Order By: Relevance
“…The regulation of IL-12 mRNA expression has been described extensively in a recent review (69) and is dependent upon the coordinated expression of IL-12 IL-12b and IL-12a genes, which are encoded on different chromosomes. Many studies have confirmed that the primary regulatory step for the expression of both IL-12 IL-12b and IL-12a genes is at the level of transcription: multiple transcription factors are known to be involved in regulation of these genes, e.g., NF-B (47), C/EBP␤ (41), PU.1 (70), IRF-1 (37, 71), IRF-2 (37), IRF-8/ICSBP (50,51), NFAT (72), AP-1 (73), and activator and repressor factors such as Kruppellike factor (74). TLR-mediated NF-B binding and translocation is dependent upon the degradation of an inhibitory protein, IB␣.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of IL-12 mRNA expression has been described extensively in a recent review (69) and is dependent upon the coordinated expression of IL-12 IL-12b and IL-12a genes, which are encoded on different chromosomes. Many studies have confirmed that the primary regulatory step for the expression of both IL-12 IL-12b and IL-12a genes is at the level of transcription: multiple transcription factors are known to be involved in regulation of these genes, e.g., NF-B (47), C/EBP␤ (41), PU.1 (70), IRF-1 (37, 71), IRF-2 (37), IRF-8/ICSBP (50,51), NFAT (72), AP-1 (73), and activator and repressor factors such as Kruppellike factor (74). TLR-mediated NF-B binding and translocation is dependent upon the degradation of an inhibitory protein, IB␣.…”
Section: Discussionmentioning
confidence: 99%
“…There have been hints of EKLF expression in macrophage (Luo et al, 2004), although our analysis of adult bone marrow hematopoietic material had shown no evidence (Frontelo et al, 2007). To address this we used the mouse strain derived from ESCs that contain a single copy of the EKLF promoter directly upstream of a GFP reporter, integrated into the HPRT locus ( Fig.…”
Section: Eklf Regulation Of Relevant Targets In Erythroblastic Islandsmentioning
confidence: 99%
“…The cDNAs were amplified with 35 cycles of PCR using the Phusion polymerase (NEB, Frankfurt am Main, Germany, http://www.neb-online.de/de/) under the following conditions: denaturation for 10 seconds at 98 C, primer annealing for 30 seconds at the temperature of 50 C, and primer extension for 1 minute at 72 C. SiRNA-mediated knockdown of human ERK, PKCd, and PU.1 in HeLa cells was performed by transfection of RNA duplexes: MAPK/ERK: Hs_MAPK3_5/Hs_MAPK1_10 siRNA (SI00300776, SI00300755; Qiagen) PKCd: Hs_PRKCD_7 siRNA (SI00301329; Qiagen). For PU.1 silencing, we used a PU.1-specific siRNA with the target sequence 5 0 -AAGCTCACCT ACCAGTTC-3 0 (Eurofins MWG Biotech, Ebersberg, Germany, http://www.eurofinsdna.com/de/home.html?gclid¼CI_ZkIXg4aUCFQGHDgodx Rmc0Q) as previously described [22]. For control, a nonspecific siRNA with the target sequence 5 0 -AAUUCUCCGAACGUGU-CACGT-3 0 was used (1022076; Qiagen).…”
Section: Rt-pcr and Sirnasmentioning
confidence: 99%